From CCS to CSP: the m-among-n Synchronisation Approach - Butterfield, Andrew; Ekembe Ngondi, Gerard; Koutavas, Vasileios (Open Publishing Association, 2022)
We present an alternative translation from CCS to an extension of CSP based on m-among-n syn chronisation (called CSPmn). This translation is correct up to strong bisimulation. Unlike the g-star renaming approach ([4]), this translation is not limited by replication (viz., recursion with no nested parallel composition). We show that m-among-n synchronisation can be implemented in CSP based on multiway synchronisation and renaming.
Electronic Proceedings in Theoretical Computer Science
Combined 29th International Workshop on Expressiveness in Concurrency and 19th Workshop on Structural Operational Semantics
Keywords: CONCURRENCY THEORY; FORMAL VERIFICATION; Formal Methods; Formal Semantics